Shannon entropy applied to the measurement of the electroencephalographic effects of desflurane. - Bruhn, J; Lehmann, L E; Röpcke, H; Bouillon, T W; Hoeft, A (Anesthesiology, 2001)
Background: The Shannon entropy is a standard measure for the order state of sequences. It quantifies the degree of skew of the distribution of values. Increasing hypnotic drug concentrations increase electroencephalographic amplitude. The probability density function of the amplitude values broadens and flattens, thereby changing from a skew distribution towards equal distribution. We investigated the dose-response relation of the Shannon entropy of the electroencephalographic amplitude values during desflurane monoanesthesia in comparison with previously used electroencephalographic parameters.Methods: Electroencephalographic records previously obtained in 12 female patients during gynecologic laparotomies were reanalyzed. Between opening and closure of the peritoneum, desflurane vapor settings were varied between 0.5 and 1.6 minimum alveolar concentration. Electroencephalographic Shannon entropy, approximate entropy, median electroencephalographic frequency, SEF 95, total power, log total power, and Bispectral Index were determined, and their correlations with the desflurane effect compartment concentration, obtained by simultaneous pharmacokinetic-pharmacodynamic modeling, were compared.Results: The electroencephalographic Shannon entropy increased continuously over the observed concentration range of desflurane. The correlation of the Shannon entropy (R2 = 0.84+/-0.08, mean +/- SD) with the desflurane effect compartment concentrations is similar to approximate entropy (R2 = 0.85+/-0.12), SEF 95 (R2 = 0.85+/-0.10), and Bispectral Index (R2 = 0.82+/-0.13) and is more statistically significant than median frequency (R2 = 0.72+/-0.17), total power (R2 = 0.67+/-0.18), and log total power (R2 = 0.80+/-0.09).Conclusions: The Shannon entropy seems to be a useful electroencephalographic measure of anesthetic drug effect.